Elucidation of interactions between gelatin aggregates and hsian-tsao gum in aqueous solutions. (30th July 2020) - You, Gang; Niu, Gaigai; Long, Hairong; Zhang, Chenxiao; Liu, Xiaoling
Highlights: The formation of gelatin aggregates-HG complexes was suggested. HG concentration, pH and ionic strength affected the complexes formation. The microstructure of formed complexes was tailored by pH and HG concentration. The structure of gelatin aggregates was changed after interaction with HG. Abstract: Interactions between gelatin aggregates (G, 0.5 wt%) and an anionic polysaccharide hsian-tsao gum (HG, 0–0.25 wt%) in aqueous solutions were investigated at 25 °C using zeta potentiometry, turbidimetric analysis, dynamic light scattering, confocal laser scanning microscopy (CLSM), fluorescence spectra and circular dichroism measurements. The results indicated that soluble and insoluble G-HG complexes formed mainly through electrostatic interactions followed critical pH-dependent structure-forming events. The phase transition points (pHφ1, pHopt and pHφ2 ) shifted to lower pH with HG increased, whereas pHc kept constant. Conformational transitions of G from α-helix to β-sheet were promoted by interacting with HG, concurrent with changes in environment of hydrophobic residues. Additionally, CLSM evidenced phase transitions of G from homogeneity to separation occurred by interaction with HG, forming G-HG complexes with G centered and HG absorbed on the periphery. Findings aided in understanding interactions mechanism between G and HG to further apply HG in designing new food matrixes.